Beryllium erosion and redeposition in ITER H, He and D–T discharges. (24th January 2022) - Romazanov, J.; Kirschner, A.; Brezinsek, S.; Pitts, R.A.; Borodin, D.; Rode, S.; Navarro, M.X.; Schmid, K.; Veshchev, E.; Neverov, V.S.; Kukushkin, A.B.; Alekseev, A.G.; et al.
Abstract: The Monte-Carlo code ERO2.0 was used to simulate steady-state erosion and transport of beryllium (Be) in the ITER main chamber. Various plasma scenarios were tested, including a variation of the main species (hydrogen, deuterium, helium), plasma conditions (density, temperature, flow velocity) and magnetic configurations. The study provides valuable predictions for the Be transport to the divertor, where it is expected to be an important contributor to dust formation and fuel retention due to build-up of co-deposited layers. The Be gross and net erosion rates provided by this study can help identifying first wall regions with potentially critical armour lifetime.